2015
DOI: 10.1016/j.brat.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among adaptive and maladaptive emotion regulation strategies and psychopathology during the treatment of comorbid anxiety and alcohol use disorders

Abstract: Both maladaptive and adaptive emotion regulation strategies have been linked with psychopathology. However, previous studies have largely examined them separately, and little research has examined the interplay of these strategies cross-sectionally or longitudinally in patients undergoing psychological treatment. This study examined the use and interplay of adaptive and maladaptive emotion regulation strategies in 81 patients receiving cognitive-behavioral interventions for comorbid alcohol use and anxiety dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 44 publications
1
30
1
Order By: Relevance
“…For example, the results suggest that targeting emotion dysregulation in the context of anxiety and hazardous alcohol use among Latinos may be one therapeutic strategy to reduce severity of alcohol use (and hazardous drinking). Past work has found that emotion dysregulation is a malleable construct and that improvements in some emotion regulation strategies are associated with lower rates of psychopathology post‐treatment . As such, therapies developed with an emphasis on emotion regulation may be useful in reducing alcohol use severity/hazardous drinking among Latinos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the results suggest that targeting emotion dysregulation in the context of anxiety and hazardous alcohol use among Latinos may be one therapeutic strategy to reduce severity of alcohol use (and hazardous drinking). Past work has found that emotion dysregulation is a malleable construct and that improvements in some emotion regulation strategies are associated with lower rates of psychopathology post‐treatment . As such, therapies developed with an emphasis on emotion regulation may be useful in reducing alcohol use severity/hazardous drinking among Latinos.…”
Section: Discussionmentioning
confidence: 99%
“…Theoretical models suggest that emotion dysregulation in the context of elevated anxiety symptoms may lead to psychological disorders, such as, anxiety/depressive disorders and substance use disorders . In line with such work, improvements in emotion dysregulation over the course of treatment are associated with reduced post‐treatment psychopathology among comorbid anxiety/alcohol use disorder patients . Thus, persons may experience emotion dysregulation when anxious, and consequently, engage in use of alcohol as a coping strategy.…”
Section: Introductionmentioning
confidence: 94%
“…Such an approach would be consistent with intervention work on emotion dysregulation and alcohol use disorders among non-HIV samples (e.g., Berking et al, 2011). For example, changes in the use of maladaptive emotion regulation strategies over the course of treatment have been shown to predict changes in anxiety- and alcohol-related psychopathology in a sample with comorbid anxiety and alcohol use disorders (Conklin et al, 2015). Given that newer treatments directly targeting emotion regulation are mounting growing evidence in treating a range of emotional outcomes (Gratz, Weiss, & Tull, 2015), such treatments may serve as additional options for the treatment of hazardous drinking among PLWHA.…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach would be consistent with intervention work on emotion dysregulation and substance use (e.g., Berking et al, 2011). For example, changes in the use of maladaptive emotion regulation strategies over the course of treatment have been shown to predict changes in anxiety/stress and alcohol-related psychopathology (Conklin et al, 2015). It is possible that tailoring these treatments to smokers with insomnia would offer a novel and more personalized approach to improve behavioral health and change smoking behavior.…”
Section: Discussionmentioning
confidence: 99%